Rotavirus genotypes and clinical outcome of natural infection based on vaccination status in the post-vaccine era - Kei Kozawa; Yuki Higashimoto; Yoshiki Kawamura; Hiroki Miura; Takumi Negishi; Fumihiko Hattori; Masaru Ihira; Satoshi Komoto; Koki Taniguchi; Tetsushi Yoshikawa (Human Vaccines & Immunotherapeutics, 2022)
Rotavirus (RV) is a leading cause of gastroenteritis in children. In Japan, Rotarix (RV1; GlaxoSmithKline), which is a monovalent vaccine derived from human RV (G1P[8]), has been introduced since November 2011, and RotaTeq (RV5; MSD) which is an pentavalent, human-bovine mono-reassortant vaccine (G1, G2, G3, G4, and P1A[8]), has been introduced since July 2012. Long-term follow-up on vaccine efficacy and RV genotypical change should be carried out in order to control RV infection. The RV gastroenteritis (RVGE) outbreak occurred during the 2018/2019 season in Aichi prefecture, Japan. Therefore, the molecular epidemiology of RV among three different groups of RVGE, which were outpatients who received RV1, those who received RV5, and those without vaccination, was explored. Clinical features of RVGE patients were compared among the three patient groups. Children less than 15 years of age with gastroenteritis who visited any of seven pediatric practices between January and June 2019 were enrolled in the study. G, P, and E genotypes were determined by direct sequencing of reverse transcription–polymerase chain reaction products amplified from stool samples. Among 110 patients, there were 27, 28, and 55 in the RV1-vaccinated, RV5-vaccinated, and unvaccinated groups, respectively. The most frequent genotype was G8P[8] (92/110 patients, 83.6%). Genotype distributions did not significantly differ among the three patient groups (P = .125). Mean Vesikari score was significantly lower among RV1-vaccinated (7.1) and RV5-vaccinated patients (6.4) than among unvaccinated patients (10.2) (P < .001). Even in RVGE patients treated in an outpatient clinic, RV vaccine reduced the severity of the disease in this cohort.